ANALISIS DESKRIPSI KEBIJAKAN PENERAPAN PENGGUNAAN PIRANTI LUNAK YANG LEGAL DAN OPEN SOURCE SOFTWARE DI LINGKUNGAN INSTANSI PEMERINTAH - Mgs. Hendri (Jurnal Informatika Terpadu, 2015)
The government, since June 30, 2004, has declared IGOS! Indonesia Go Open Source Software through its five ministries. Minister of Communication and Information, Minister of Research and Technology, Minister of Empowerment of State Apparatus, Minister of National Education, and Minister of Law and Human Rights to use legal and open computer software within government agencies. This does accelerate good governance, efficiency, and accountability to the public. The declaration agrees that all government agencies must implement and utilize legal software applications. Legal software can be in software applications based on Open Source Software (open source code) or proprietary (closed source code). This effort is in line with law enforcement and legal software, both Open Source Software and proprietary in all circles. For this reason, the government, through the Minister of Communication and Information, has issued Circular Letter Number: 05/SE/M.KOMINFO/10/2005 concerning the Use and Utilization of Legal Software in Government Agencies.